Synthetic Applications of Symmetrical Disulfides and Their Synthesis from Non-thiolic Substrates - Kim, Kyungmi; Chae, Junghyun (Synthesis, 2025)
Organic disulfides are frequently found in many fields of science, ranging from chemistry to materials science to biology. While symmetrical disulfides, which have the same substitutions on the two sulfurs, are often final products, they are mostly employed as reactants and catalysts in various reactions. In addition to their usage as catalysts, their synthetic applications as reactants can arbitrarily be categorized into three types: (1) surrogates for the corresponding thiols, (2) reactants for unsymmetrical disulfides, and (3) reactants or intermediates for the other compounds. Although the straightforward, traditional way to obtain symmetrical disulfides (RSSR) is the oxidation of their parental thiols (RSH), they can also be obtained from non-thiolic compounds. This short review covers representative synthetic applications of symmetrical disulfides and their preparation methods in which the starting materials are not the corresponding thiols.1 Introduction2 Synthetic Applications of Symmetric Disulfides2.1 Surrogates for Thiols2.2 Synthesis of Unsymmetrical Disulfides2.3 As Reactants and Intermediates3 Synthesis of Symmetrical Disulfides from Non-thiolic Substrates3.1 Synthesis from Organic Halides3.2 Synthesis from Sulfonic Acid Derivatives3.3 Synthesis from Sulfinic Acid Derivatives3.4 Miscellaneous4 Conclusion
Keywords: symmetrical disulfide; unsymmetrical disulfide; thiol surrogate; sulfanylation; cross-coupling